A COMPARATIVE STUDY OF PAPER-BASED MICROFLUIDIC (µPAD) MINIATURIZATION - Badril Azhar; Faisal Amir; Aditya Sukma Nugraha; Hakun W. Aparamarta (Jurnal PPI Dunia, 2022)
In recent years, paper-based analytical devices gained more attention for development of low-cost point-of-care diagnostic tools in many fields, such as environmental testing, point of care diagnosis, and food analysis. In the present study, we introduce a new paper substrate (Xuan paper) and compare to commercial filter paper (whatman) with hydrophobic materials called polydimethylsiloxane (PDMS). The xuan paper can be used for paper-based microfluidics analytical devices (μPAD) and that flow rate is reliant on many factors affecting fluid flow inside the channels. The screen-printing method was used to concocted hydrophobic channels by patterning hydrophobic materials onto paper substrate with the patterned channels reaching a minimum width of 0.2 mm and maximum 5 mm. The fabricated channels were tested by using water with different paper types and different channel widths. The experimental results were compared with commercially available filter paper (11 and 21 µm pore size). The results of this study are raw xuan paper (0.15 mm of thickness) is similar trend with filter paper (0.21 mm of thickness) about 43 mm distance in 140 second and it is higher than three other papers. However, jinghe paper (0.13 mm of thickness) and cotton xuan paper (0.10 mm of thickness) shows the distance of water about 10 mm and 4 mm, respectively in 140 second because of their fiber orientation and water being absorbed by it. Therefore, xuan paper was a good candidate in applied for µPAD application.